A review of the quality of primary caregiver-implemented communication intervention research for children with ASD. (May 2016) - Hong, Ee Rea; Ganz, Jennifer B.; Neely, Leslie; Gerow, Stephanie; Ninci, Jennifer
Highlights: This study presents a literature review of caregiver-implemented interventions for improving communication skills of children with ASD. The quality of the research design for caregiver-implemented communication interventions for children with ASD was evaluated. A total of 40 studies were identified to meet the design standards and included in this review. About one-third of studies included in this review was found to meet the design standards. The studies that failed to meet the design standards were mainly due to a lack of IOA collected with the minimum quality thresholds. Abstract: Background: Most children with autism spectrum disorder (ASD) spend most of their waking hours at home with their caregivers; thus, involving caregivers in interventions may increase communication interaction opportunities across time and settings. Method: In this review, an analysis of the quality of the research on communication interventions implemented or mediated by caregivers of children with ASD was conducted based on the What Works Clearinghouse guidelines (Kratochwill et al., 2010 ) and adapted byMaggin et al. (2013) . Results: About one-third of studies included in this review were found to meet the design standards, indicating that those studies utilized a high quality of research design. The studies that failed to meet the design standards were primarily those that lacked sufficient interobserver agreement data collected in each condition, thus, not meeting the minimum quality thresholds. To evaluate an overall effectiveness, a total of 31 single-case experiments were evaluated with the evidence standards. As a result, about half of the experiments were found to have either strong or moderate evidence of an effect. Conclusions: The findings in this review suggest issues that need to be addressed in the field related to quality of designs in single-case research on primary caregiver-implemented communication interventions for children with ASD. Limitations and implications for future research and for practitioners are discussed.